2016
DOI: 10.1038/srep35263
|View full text |Cite
|
Sign up to set email alerts
|

New potential beneficial effects of actein, a triterpene glycoside isolated from Cimicifuga species, in breast cancer treatment

Abstract: Actein is a triterpene glycoside isolated from the rhizomes of Cimicifuga foetida (Chinese herb “shengma”) which could inhibit the growth of breast cancer cells. Nevertheless, the effect of actein on angiogenesis, which is an essential step for tumor growth and metastasis, has never been reported. Hence, this study aimed to investigate the in vitro and in vivo effects of actein on angiogenesis using human microvascular endothelial cells (HMEC-1), matrigel plug and tumor-bearing mouse models. Our results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 55 publications
1
37
0
Order By: Relevance
“…The study moreover found that the p53-dependent mitochondrial signaling pathway contributes to the mechanism of apoptosis. A more recent study in a murine breast tumor-bearing model demonstrated that actein (1) exhibits anti-angiogenic and immunomodulatory effects and decreased tumor size and metastasis in lung and liver [19].…”
Section: Introductionmentioning
confidence: 99%
“…The study moreover found that the p53-dependent mitochondrial signaling pathway contributes to the mechanism of apoptosis. A more recent study in a murine breast tumor-bearing model demonstrated that actein (1) exhibits anti-angiogenic and immunomodulatory effects and decreased tumor size and metastasis in lung and liver [19].…”
Section: Introductionmentioning
confidence: 99%
“…Actein is a widely studied natural triterpene glycoside that has recently attracted attention in breast cancer due to its effects on various biological processes in cancer 16, 4749 . In this study, cell death and cell cycle roles of TGF-beta, PI3K-Akt-mTOR and NRF2 pathways were up-regulated while proliferation roles of TGF-beta pathway were down-regulated.…”
Section: Discussionmentioning
confidence: 99%
“…Embryonic stem cell-expressed RAS was identified as a potent oncogenic driver in the HER2-positive MMTV model, acting via hyperactivation of the phosphatidylinositol-3-kinase/AKT/mammalian target of rapamycin (PI3K/AKT/mTOR) pathway, which stimulates tumor cell proliferation and metastasis and induces therapy resistance 70,71 . Recently, actein was identified as an effective inhibitor of the PI3K/AKT/mTOR pathway, showed anti-angiogenic effects in vitro, and decreased breast tumor size and metastasis in vivo 72,73 . CR activated AMP-activated protein kinase, which is known to inhibit mTOR 74 .…”
Section: Safety Of Icr/icr 1 Hp After Breast Cancerexperimental Datamentioning
confidence: 99%